Distillation sieve tray efficiencies - Kalbassi, Mohammed Ali (1987)
The distillation point efficiencies for the alcohol-water binary, ternary and quaternary systems were measured using a modified Oldershaw column. This column is expanded above the tray to separate the newly formed bubbles from the column wall, thus eliminating the surface tension induced wall effects for positive systems and discouraging wetted wall effects. The excessive and recirculating foam and froth found in the conventional Oldershaw column is due to these wall effects and does not represent conditions in large scale distillation.